Immunogenicity of BNT162b2 Vaccine Booster Dose in Patients With Inflammatory Bowel Disease Receiving Infliximab Combination Therapy: A Prospective Observational Study - Shehab, Mohammad; Alrashed, Fatema; Alfadhli, Ahmad; Alsayegh, Abdulwahab; Aldallal, Usama; Alsayegh, Mariam; Cherian, Preethi; Alkhair, Irina; Thanaraj, Thangavel Alphonse; Channanath, Arshad; Dashti, Ali A.; Albanaw, Anwar; et al. (Frontiers in Medicine, 2022)
Introduction Few data exist regarding the immunogenicity of the third dose of BNT162b2 relative to the second dose in patients with inflammatory bowel disease (IBD) on different immunosuppressive therapies. We investigated the immunogenicity of BNT162b2 vaccine booster dose in patients with IBD on infliximab combination therapy. Method This is a prospective single-center observational study conducted from January 1, 2022 to February 28, 2022. Patients were recruited at the time of attendance at the infusion center. Eligibility criteria included patients with a confirmed diagnosis of IBD who are receiving infliximab with azathioprine or 6-mercaptopurine. Patients who received two doses of BNT162b2 vaccine (second dose group) were compared to patients who had received three doses of BNT162b2 vaccine [third dose (booster) group]. Patients were excluded if they were infected or had symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) previously since the start of the pandemic or received other vaccines than the BNT162b2. Our primary outcome was the concentrations of SARS-CoV-2 antibodies Immunoglobulin G (IgG) and neutralizing antibodies 40–45 weeks from the first dose of BNT162b2 vaccine in patients with IBD receiving infliximab combination therapy. Medians with interquartile range (IQR) were calculated. Results In total, 162 patients with IBD and receiving infliximab combination therapy were recruited, and the number of patients in both the second dose group and third dose (booster) group was 81. Mean age was 35 years old in both groups. Median (IQR) SARS-CoV-2 IgG levels were significantly lower after the second dose [125 BAU/ml (43, 192)] compared to patients who received the third booster dose [207 BAU/ml (181, 234)] (P = 0.003). Neutralizing antibody levels were also lower after the second dose [80% (21, 95)] compared to patients who received the third booster dose [96% (93, 99)] (P ≤ 0.001). The percentage of patients who achieved positive SARS-CoV-2 IgG levels in the third (booster) dose group was 96.3%, whereas it was 86.4% in the second dose group. The percentage of participants who received the third (booster) dose and achieved a positive SARS-CoV-2-neutralizing antibody level was 100%, whereas it was 88.9% in the participants who received the second dose only. Conclusion Most patients with IBD on infliximab combination therapy had positive SARS-CoV-2 IgG and neutralizing antibody concentrations 40–45 weeks post BNT162b2 vaccination. However, SARS-CoV-2 IgG and neutralizing antibody concentrations were lower in patients who received two doses only compared to patients who received a third dose. A longer follow-up study is needed to evaluate decay in antibodies over time.